(untitled) (International Journal of Physiotherapy, 2015)
Background: The elderly population is growing, both in size and proportion with the total population and fall is a major problem for elderly. The aim of this study was to determine the prevalence and correlates of falls among elderly. Methodos: A cross sectional survey with Snowball sampling technique was used to recruit 100 elderly persons, 52 male and 48 female, 65 years and above. A modified self administered closed ended questionnaire was used. The data obtained were summarized using descriptive statistics of mean and Standard Deviation. Inferential statistics of Chi square, phi and Cramer’s V were used to analyze the data. Result: The result showed that 49% of the elderly had one or more falls with 65.3%falls occurring once and 34.7% occurring two or more times. Women fall more than men, accounting for 61.2% and 38.8% of the population respectively. A significant association was found between fall, age, sex, and reduced balance. Conclusion: The study concluded that there is high prevalence of falls in elderly with women experiencing more fall than men. It is recommended that modifications in the environment, counseling to the elderly and their families should be done to prevent further falls.